DIAGNOSIS OF ENDOCRINE DISEASE: Evaluation of bone fragility in endocrine disorders. Issue 6 (June 2019) - Eller-Vainicher, Cristina; Falchetti, Alberto; Gennari, Luigi; Cairoli, Elisa; Bertoldo, Francesco; Vescini, Fabio; Scillitani, Alfredo; Chiodini, Iacopo
Abstract : An underlying disease affecting bone health is present in up to 40 and 60% of osteoporotic postmenopausal women and men respectively. Among the disorders leading to a secondary form of osteoporosis, the endocrine diseases are highly represented. A frequent finding in patients affected with an endocrine-related forms of bone disease is that the skeletal fragility is partially independent of the bone density, since the fracture risk in these patients is related more to a reduction of bone quality than to a decrease of bone mass. As a consequence, bone mineral density evaluation by dual-X-ray absorptiometry may be inadequate for establishing the risk of fracture in the setting of the endocrine-related forms of osteoporosis. In the recent years, several attempts to non-invasively estimating bone quality have been done. Nowadays, some new tools are available in the clinical practice for optimising the fracture risk estimation in patients with endocrine disorders. The aim of this review is to summarise the evidence regarding the role of the different imaging tools for evaluating bone density and bone quality in the most frequent forms of endocrine-related osteoporosis, such as obesity, diabetes, acromegaly, thyrotoxicosis, primary hyperparathyroidism, hypercortisolism and hypogonadism. For each of these disorders, data regarding both the current available tools and the future possible new techniques for assessing bone fragility in patients with endocrine diseases are reported.